DANAKANG : NATURAL INSTINCTS AND STRENGTHENING MARITIME EDUCATION FOR BAJO TRIBE CHILDREN - Early Wulandari Muis; Indra Rahayu Setiawati Togala; Husni Halim (International Conference on Social and Islamic Studies, 2021)
The participation of school-age Bajo Tribe children in formal education (school) is still relativelylow. Parents there perceive school education less important. Most of them believe that children only needto know how to read, write, and count. They rather put more emphasis on informal family education(danakang). This study determined a strategy of family intervention through fundraising. In-depthobservations and interviews were conducted to members of Bajo Tribe in Bungin Permai Village,Southeast Sulawesi. The results showed that informal family education (danagang) has been conductedthrough storytelling, and children have been actively involved in performing fishermen’s jobs. Parentshave been educating their children about waves (goyya), seasons (Tempo'), coral islands (Sappa), wind (Sangei) and weather, different fishing equipment and how to build a boat (Leppa). It can be inferred thatinformal family education (danakang) is a way for members of Bajo Tribe to preserve their identity aspeople who are close to the sea, while at the same time strengthening the education system inheritedthrough maritime cultural traditions.